2015
DOI: 10.1037/pspp0000049
|View full text |Cite
|
Sign up to set email alerts
|

Self-esteem, narcissism, and stressful life events: Testing for selection and socialization.

Abstract: We examined whether self-esteem and narcissism predict the occurrence of stressful life events (i.e., selection) and whether stressful life events predict change in self-esteem and narcissism (i.e., socialization). The analyses were based on longitudinal data from 2 studies, including samples of 328 young adults (Study 1) and 371 adults (Study 2). The effects of self-esteem and narcissism were mutually controlled for each other and, moreover, controlled for effects of depression. After conducting the study-lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
86
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(108 citation statements)
references
References 118 publications
12
86
1
2
Order By: Relevance
“…Alternatively, this may be a transitional profile that many people fall into at some point within their life-span, perhaps after experiencing negative life events, but move out of over time. Similarly, while the narcissistic self-esteem class currently has high self-esteem, they may not in the future (Orth & Luciano, 2015), particularly considering that narcissists' self-esteem is more reactive to external events and shows more fluctuation (Morf & Rhodewalt, 2001). Finally, there remains the question of whether membership in the narcissistic self-esteem profile is growing over time, as narcissism has been found to be increasing in some research (Twenge, 2013), but remaining stable in others (Trzesniewski & Donnellan, 2010).…”
Section: Strengths and Future Directionsmentioning
confidence: 90%
See 1 more Smart Citation
“…Alternatively, this may be a transitional profile that many people fall into at some point within their life-span, perhaps after experiencing negative life events, but move out of over time. Similarly, while the narcissistic self-esteem class currently has high self-esteem, they may not in the future (Orth & Luciano, 2015), particularly considering that narcissists' self-esteem is more reactive to external events and shows more fluctuation (Morf & Rhodewalt, 2001). Finally, there remains the question of whether membership in the narcissistic self-esteem profile is growing over time, as narcissism has been found to be increasing in some research (Twenge, 2013), but remaining stable in others (Trzesniewski & Donnellan, 2010).…”
Section: Strengths and Future Directionsmentioning
confidence: 90%
“…Recent research suggests that both high narcissism and low self-esteem can lead to the experience of stressful life events, which in turn cause low self-esteem (Orth & Luciano, 2015). Therefore, belonging to the low self-regard profile or the narcissistic self-esteem profile may be related to low self-esteem over time.…”
Section: Strengths and Future Directionsmentioning
confidence: 98%
“…There is currently a glaring lack of knowledge on the developmental trajectories of narcissism in adulthood, let alone on the specific conditions that may influence it (Grijalva & Harms, 2014;Orth & Luciano, 2015;Tasselli et al, 2018). With regard to narcissism development, some preliminary research has demonstrated age differences in narcissism, showing that older people tend to score lower on narcissism compared to younger people (Foster, Campbell, & Twenge, 2003;Roberts, Edmonds, & Grijalva, 2010).…”
Section: Reciprocal Relationships Over Two Decadesmentioning
confidence: 99%
“…Instead, such age differences have mainly been used to inform the debate on the (non-)existence of generational differences in narcissism (e.g., Roberts et al, 2010;Trzesniewski, Donnellan, & Robins, 2008a;2008b). In addition to this cross-sectional work, and more relevant to the current study, a handful of investigations have looked at within-person changes in narcissism using longitudinal designs in which participants are tracked across several years during young adulthood (i.e., under age 30) (Carlson & Gjerde, 2009;Grosz et al, 2019;Orth & Luciano, 2015). Across all three studies, virtually no mean-level intraindividual change in narcissism was observed during early adulthood.…”
Section: Reciprocal Relationships Over Two Decadesmentioning
confidence: 99%
“…‫ﺑﻪ‬ ‫ﻧﻔﺲ‬ ‫ﻋﺰت‬ ‫ﺧﻮد‬ ‫درﺑﺎره‬ ‫ﻓﺮد‬ ‫ﮐﻪ‬ ‫ﻋﺎﻃﻔﯽ‬ ‫و‬ ‫ﺷﻨﺎﺧﺘﯽ‬ ‫ﻣﻔﻬﻮﻣﯽ‬ ‫ﻋﻨﻮان‬ ‫ﭼ‬ ‫اﯾﻨﮑﻪ‬ ‫و‬ ‫ﺧﻮد‬ ‫ﺗﻮﺻﯿﻒ‬ ‫و‬ ‫درک‬ ‫و‬ ‫دارد‬ ‫و‬ ‫اﺣﺘﺮام‬ ‫ﺧﻮدش‬ ‫ﺑﺮای‬ ‫ﻘﺪر‬ ‫اﺳﺖ‬ ‫ﺷﺪه‬ ‫ﺗﻌﺮﯾﻒ‬ ‫اﺳﺖ‬ ‫ﻗﺎﯾﻞ‬ ‫ارزش‬ [3] ‫و‬ ‫ﻣﻮﻓﻘﯿﺖ‬ ‫ﺑﺎ‬ ‫ﻧﻔﺲ‬ ‫ﻋﺰت‬ . ‫اﺳﺘﺮس‬ ‫روﯾﺪادﻫﺎی‬ ‫ﺑﺎ‬ ‫ﻣﻘﺎﺑﻠﻪ‬ ‫ﺗﻮاﻧﺎﯾﯽ‬ ‫دارد‬ ‫ارﺗﺒﺎط‬ ‫زﻧﺪﮔﯽ‬ ‫زای‬ [4] .…”
unclassified